PROBLEMATIKA PEMBELAJARAN SEKOLAH DASAR DI MASA PANDEMI - Nur Rira Febriyani (Universitas Islam Lamongan, 2021)
During the Covid-19 pandemic, Indonesia experienced various problems, one of which was in the field of education. As an effort to prevent the spread of a pandemic, Indonesia implements social distancing or maintains a distance from one another to be very important things to do. During this pandemic, all people work at home, study from home, worship at home, and are prohibited from doing activities outside the home. This causes many schools and offices to be temporarily closed, this is not automatically accepted and carried out by the Indonesian people. This article was written by reviewing references to various online learning problems during a pandemic as a solution to continuing the learning process carried out at home during this pandemic.By using qualitative research methods using existing references, it will produce facts from learning problems that occur during the pandemic and solutions that must be done to solve these problems, so that students can participate in learning maximally even though there are many obstacles in learning at home.